One nation, more politeness strategies. The compliment as an instance of Variational Pragmatics in Italy (Atti del Sodalizio Glottologico Milanese, 2023)
Framed in variational pragmatics, this work aims at comparing the compliment management in three different regional varieties of Italian. In order to fully understand the different facework dynamics in the compliments in Piemonte Orientale, Cancello ed Arnone (Caserta) and among the Sardinian community (Biella), the compliments have been analyzed having recourse to three different models of politeness: Brown and Levinson (1987), the “Face Constituting Theory” (Arundale 2006), Mursy and Wilson’s “Social Contract of Values” (2001).